The Sonozotz project: Assembling an echolocation call library for bats in a megadiverse country - Veronica Zamora‐Gutierrez; Jorge Ortega; Rafael Avila‐Flores; Pedro Adrián Aguilar‐Rodríguez; Martín Alarcón‐Montano; Luis Gerardo Avila‐Torresagatón; Jorge Ayala‐Berdón; Beatriz Bolívar‐Cimé; Miguel Briones‐Salas; Martha Chan‐Noh; Manuel Chávez‐Cauich; Cuauhtémoc Chávez; et al. (Ecology and Evolution, 2020)
Abstract Bat acoustic libraries are important tools that assemble echolocation calls to allow the comparison and discrimination to confirm species identifications. The Sonozotz project represents the first nation‐wide library of bat echolocation calls for a megadiverse country. It was assembled following a standardized recording protocol that aimed to cover different recording habitats, recording techniques, and call variation inherent to individuals. The Sonozotz project included 69 species of echolocating bats, a high species richness that represents 50% of bat species found in the country. We include recommendations on how the database can be used and how the sampling methods can be potentially replicated in countries with similar environmental and geographic conditions. To our knowledge, this represents the most exhaustive effort to date to document and compile the diversity of bat echolocation calls for a megadiverse country. This database will be useful to address a range of ecological questions including the effects of anthropogenic activities on bat communities through the analysis of bat sound.